Survival of healthy older people. Issue 4 (December 1976) - Anderson, F; Cowan, N R
Abstract : The purpose of this study was to discover any relationships which might exist between measurable variables recorded when a healthy group of men and women, aged 70 years and over, were examined and their subsequent survival time. It was found that height, body weight, systolic and diastolic blood pressures, haemoglobin, hand grip power, cardiothoracic ratio, and pulse rate are of no predictive value in the estimation of survival time. Survival is not influenced by marital status or occupational class. For both sexes the degree of kyphosis and age are useful predictive criteria in respect of survival time. However, much research work requires to be done to explain why many people die at the time they do.